2011
DOI: 10.1021/jp110675e
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-Induced Collapse in Double-Walled Carbon Nanotubes: Chemical and Mechanical Screening Effects

Abstract: The vibrational properties of double-walled carbon nanotubes (DWNTs) is investigated by high-pressure resonance Raman scattering up to 30 GPa in two different pressure-transmitting media (PTM): paraffin oil and NaCl. The protection effect on the outer tube during compression is verified .The collapse of DWNTs is experimentally observed for the first time, showing to be two-step: the onset of the outer 1.56 nm diameter tube collapse at ∼21 GPa is followed by the collapse of the inner 0.86 nm diameter tube at a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
109
3

Year Published

2012
2012
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(128 citation statements)
references
References 31 publications
13
109
3
Order By: Relevance
“…Raman spectroscopy has been broadly used to study effects caused by strain, majorly focusing on the G band behaviour on SWNT bundles [74][75][76][77][78][79][80]. Combination of AFM with confocal Raman spectroscopy was made to follow, in situ, the evolution of the SWNT structure with transversal pressure applied to the tube.…”
Section: Pushing the Limits Of Raman Spectroscopy Applications On Sp mentioning
confidence: 99%
“…Raman spectroscopy has been broadly used to study effects caused by strain, majorly focusing on the G band behaviour on SWNT bundles [74][75][76][77][78][79][80]. Combination of AFM with confocal Raman spectroscopy was made to follow, in situ, the evolution of the SWNT structure with transversal pressure applied to the tube.…”
Section: Pushing the Limits Of Raman Spectroscopy Applications On Sp mentioning
confidence: 99%
“…It has been demonstrated that the homogeneous filling of the SWCNT cavity with an inner wall, forming what is called a double-walled carbon nanotube (DWCNT), stabilizes the outer tube [8][9][10][11][12][13]. In contrast, filling SWCNTs with C 70 or iodine molecules, which is considered as a case of inhomogeneous filling, leads to the destabilization of the nanotubes [8,10,11,14,15]. This was attributed to the inhomogeneous interaction, i.e., van der Waals forces, between the nanotube wall and the inner filler.…”
Section: Introductionmentioning
confidence: 99%
“…High-pressure Raman measurements showed that in the case of double-walled carbon nanotubes (DWCNTs) the inner tube supports the outer one up to high pressure before the collapse. 7,8 On the contrary, iodine and C 70 fillers are supposed to cause a destabilization of the SWCNTs. 6,7 Up to now, the stability of SWCNTs and DWCNTs against hydrostatic pressure has been mainly addressed by Raman spectroscopy, which monitors the vibrational properties.…”
Section: Introductionmentioning
confidence: 99%
“…Several earlier experimental studies (mostly Raman) reported higher critical pressures for the structural transition of the outer tube in DWCNTs as compared to SWCNTs, and this was attributed to the structural support of the outer tube by the inner tube. 7,30,34 The enhanced structural stability of the outer tube was theoretically predicted by Yang et al 35 : For small-diameter (5,5)(10,10) DWCNT bundles (d inner ≈0.68 nm, d outer ≈1.36 nm) a small discontinuous volume change appears at the critical pressure P d =18 GPa, accompanied by a cross sections' change between two deformed hexagons; the collapse to peanut shaped cross sections, however, happens at higher pressure. In contrast, (7,7)(12,12) DWCNT bundles (d inner ≈0.95 nm, d outer ≈1.63 nm) undergo one structural phase transition and collapse at P d =10.6 GPa.…”
mentioning
confidence: 99%